Implementation of Religious Character Education in Coping with Student Bullying Behavior (Implementasi Pendidikan Karakter Religius dalam Menanggulangi Perilaku Bullying Siswa) - La Hadisi (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to analyze the potential for bullying behavior of Islamic Islamic students in the city of Kendari, the implementation of religious character education in tackling the bullying behavior of students of Madrasah Ibtidayah 1, and the private Asy-Syafi'iyah Madrasah in Kendari, as well as the obstacles and efforts in implementing character education. religious. By using a qualitative approach, data were collected through interviews, observations and documents. The results showed: (1) Student bullying behavior occurred in the form of physical bullying, verbal bullying and social bullying. The contributing factors are the characteristics of students, family factors, the influence of social media, and economic factors; (2) Implementation of religious character education in tackling the occurrence of bullying behavior among students of Madrasah Ibtidayah in Kendari city through several activities, namely: learning activities, routine and spontaneous activities, additional or extracurricular activities; (3) The obstacles in implementing religious character education are the lack of parental support, and students have different characters and backgrounds. Efforts are being made to build intensive communication with parents, using different methods and approaches in inculcating character values; and providing supporting infrastructure such as mosques or prayer rooms with complete facilities, halls, classrooms and Islamic schools with Islamic nuances.Keywords: Religious Character Education, Bullying Behavior of Students